Job displacement and migrant labor market assimilation - Maria Balgova; Hannah Illing (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
This paper sheds new light on the barriers to migrants' labor market assimilation. Using administrative data for Germany from 1997-2016, we estimate dynamic difference-in-differences regressions to investigate the relative trajectory of earnings, wages, and employment following mass layoff separately for migrants and natives. We show that job displacement affects the two groups differently even when we systematically control for pre-layoff differences in their characteristics: migrants have on average higher earnings losses, and they find it much more difficult to find employment. However, those who do find a new job experience faster wage growth compared to displaced natives. We examine several potential mechanisms and find that these gaps are driven by labor market conditions, such as local migrant networks and labor market tightness, rather than migrants' behavior.
Keywords: J62; J63; J64; 330; Immigration; Job Displacement; Job Search